1989
DOI: 10.1007/bf00643510
|View full text |Cite
|
Sign up to set email alerts
|

The fatigability of two agonistic muscles in human isometric voluntary submaximal contraction: an EMG study

Abstract: During an external isometric constant torque (25% of the maximal voluntary contraction) maintained until the maximal endurance time (limit time), we analysed and compared the changes in electromyographic (EMG) activity illustrating muscular fatigue simultaneously with mechanical activity (the tangential acceleration theta") related to physiological tremor. The EMG activities recorded were of two agonistic flexors, the biceps brachii (BB) and the brachioradialis (BR) muscles and one of the main extensors, the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
31
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 12 publications
10
31
2
Order By: Relevance
“…2a). This result was consistent with those of previous investigations (Bernardi et al, 1997;Gamet and, Maton, 1989;Psek and Cafarelli, 1993;Ebenbichler et al, 1998), which have also reported a higher EMG amplitude level in the agonist than in the antagonist. It has been reported that the relatively smaller activity of the antagonist increases joint stability (Milner et al, 1995) and prevents excessive force, which could lead to joint damage during muscle contraction (Ebenbichler et al, 1998).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…2a). This result was consistent with those of previous investigations (Bernardi et al, 1997;Gamet and, Maton, 1989;Psek and Cafarelli, 1993;Ebenbichler et al, 1998), which have also reported a higher EMG amplitude level in the agonist than in the antagonist. It has been reported that the relatively smaller activity of the antagonist increases joint stability (Milner et al, 1995) and prevents excessive force, which could lead to joint damage during muscle contraction (Ebenbichler et al, 1998).…”
Section: Discussionsupporting
confidence: 94%
“…It is well known that during voluntary muscle contraction the antagonist muscles generate relatively smaller force simultaneously in the direction counter to agonist muscle activity (Smith, 1981;Gamet and Maton, 1989). Therefore, studies that measure and analyze the antagonistic muscle pairs have been performed to evaluate the physiological aspects of muscles (Shibata and Moritani, 1991;Bernardi et al, 1997;Gamet and Maton, 1989;Psek and Cafarelli, 1993;Ebenbichler et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Rutherford & Jones, 1988;Zijdewind & Kernell, 1994). The interpretation of such electrical tests is, however, complicated by the fact that ulnar nerve stimulation activates FDI simultaneously with its direct antagonist, the first palmar interosseous (Zijdewind & Kernell, 1994 (Edwards & Lippold, 1956); flexor digitorum sublimis held at 25, 50 or 75% MVC (Eason, 1960); biceps brachii and brachioradialis held at 25% MVC (Gamet & Maton, 1989)). Differences between previously published results and the present ones are particularly striking with regard to Fuglevand et al (1993), who also studied FDI and used almost the same fatiguing protocol (contraction held at 20, 35 and 65% MVC).…”
Section: Discussionmentioning
confidence: 99%
“…Such force exertions can either be prolonged, which means the muscular force is continuously sustained, whereas intermittent muscle exertions display variations in the activation levels, including stopping and starting at regular or irregular intervals (Iridiastadi & Nussbaum, 2006). Prolonged static exertions have been widely studied for the development of LMF (e.g., Rohmert, 1960;Gamet & Maton, 1989;Hunter & Enoka, 2003), and the relationship between the endurance time and isometric level of muscle effort is well established. Such exertions are known to result in the fastest onset and greatest development of muscle fatigue, compared to dynamic or intermittent exertions at similar force levels (Bigland-Ritchie & Woods, 1984;SjØgaard et al, 1986;Jonsson, 1988;Masuda et al, 1999;Iridastadi & Nussbaum, 2006).…”
Section: Task Parameters and Muscle Fatiguementioning
confidence: 99%